FORENSIC EXAMINATION OF BUILDING MATERIALS: METHODOLOGY, STANDARDS, AND PRACTICAL APPLICATION (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the methods and practical application of forensic examination of building materials in judicial proceedings. Building materials examination is a specialized branch of forensic construction-technical expertise focused on determining the composition, physical-mechanical properties, and quality indicators of materials used in construction. The study presents the examination methodology including organoleptic, laboratory, and instrumental methods, describes standard equipment used in nondestructive testing, and outlines the legal framework based on Uzbekistan’s national construction norms (ShNQ, QMQ) and international standards (GOST, ASTM). Practical case findings involving concrete, reinforced concrete, brick-masonry, steel, and timber structures are discussed. The article further analyzes the challenges of expert practice in Uzbekistan’s forensic construction sector and proposes directions for methodological development. The findings confirm that scientific examination of building materials serves as a reliable evidentiary tool in construction disputes and accident investigations, and that further integration of digital and remote-sensing technologies can substantially enhance the objectivity and reproducibility of expert conclusions.
Keywords: forensic building examination; construction materials; phase composition; non-destructive testing; concrete strength; masonry structures; steel structures; timber; quality assessment; GOST standards; ShNQ; expert conclusion; construction disputes.